(untitled) (Universitas Scientiarum, 2011)
Objective. Our study was intended to detail aspects of Centronia mutisii such as its distribution, population status and propagation, due to the anthropogenic pressure on its habitat which is restricted to a localized area in Cundinamarca and the District Capital, and because it is listed as a vulnerable species (VU) by the IUCN. Materials and methods. We identified the potential distribution of C. mutisii (niche modeling), assessed the conservation status of the population, and applied plant propagation ex situ management treatments. Results. The potential geographic distribution is restricted and until now a single population has been recorded in a locality. There is a marked edge effect on the population structure and propagation is difficult. Conclusions. We propose this species as a conservation priority due to its extremely localized distribution and population structure being affected by processes that affect its habitat, and also to begin a discussion on the reclassification of its current threat level. Decision makers should include C. mutisii in research and investment agendas to develop in situ and ex situ conservation strategies. Key words: Sumapaz; IUCN; Maxent; Cundinamarca; Colombia